El Salvador : Staff Report-Request for Purchase Under the Rapid Financing Instrument-Press Release; Staff Report; and Statement by the Executive Director for El Salvador. - International Monetary Fund. Western Hemisphere Dept. (Washington, D.C. : International Monetary Fund, 2020)
This paper discusses El Salvador's IMF Staff report on Request for Purchase Under the Rapid Financing Instrument (RCI). This assistance is expected to help El Salvador direct funds swiftly to the country's most affected sectors, including the healthcare system. El Salvador has adopted strict measures to prevent and contain the pandemic since early February-even before the first case was diagnosed-including travel restrictions, mandatory quarantine for exposed citizens, suspension of nonessential public and private sector operations, and a nationwide shelter-in-place order. The authorities' emergency response also comprises measures to mitigate the economic impact of the pandemic on the population, including through targeted cash transfers to vulnerable households and tax relief in the most affected economic sectors. IMF financing will help preserve fiscal space and catalyze significant funding from other multilateral institutions. The IMF continues to closely monitor El Salvador's situation and stands ready to provide policy advice and further support as needed.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet